A comparison of elk‐vehicle collision patterns with demographic and abundance data in the Central Canadian Rocky Mountains. Issue 12 (5th November 2022) - Gunson, Kari Elizabeth; Clevenger, Anthony Paul; Ford, Adam Thomas
Abstract: Wildlife‐vehicle collisions are a widespread phenomenon that are influenced by species behavior, abundance, and road and landscape interactions. The mortality rate of different age and sex classes can buffer or exacerbate how the population responds to vehicle collisions. We evaluated the demographic‐specific patterns of elk‐vehicle collisions in the Central Canadian Rocky Mountains. More females and adults were involved in collisions, but when compared to the sex and age of the population, males and subadults were more prone to collisions in the fall. The fat marrow content (condition) of elk was greater for road‐ and rail‐kill than predator‐killed elk indicating that vehicle collisions are an additive source of mortality. As traffic volumes increased elk collisions decreased because elk declined over the study period. Evaluation of long‐term datasets can assist in designing mitigation that target the most vulnerable demographics of a population. For example, larger more open wildlife crossing structures have shown to be more suitable for vulnerable demographics such as female grizzly bears, male ungulates, and female ungulates traveling with young. When crossing structures are not practical, demographic‐specific information can inform outreach and awareness programs that strive to elicit a favorable response from motorists ultimately avoiding collisions with animals on roads. Abstract : We evaluated the patterns of elk‐vehicle collisions in the Central Canadian Rocky Mountains to reveal population‐level impacts and inform mitigation solutions. We found that more females and adults are involved in collisions, but when compared to the sex and age of the elk population, males and subadults are more prone to collisions in the fall. These findings can assist in designing mitigation measures that target the most vulnerable demographics of a population, for example, subadults, and implementing mitigation measures before a population extinction occurs.